Hb Alesha [β67(E11)Val→Met, GTG→ATG] in an Argentinean girl - Eberle, Silvia Eandi (2007)
Hb Alesha is caused by a GTG>ATG mutation at codon 67 of the b-globin gene, resulting in abnormal beta-globin chains in which the normal beta67(E11) valine is changed to methionine. This hemoglobin (Hb) is also known as Hb Bristol, the first unstable Hb described, since in a fraction of the variant the methionine is modified into an aspartic acid by a posttranslational modification. This replacement disrupts the apolar bonds between the valine and the heme group, producing an unstable Hb and severe hemolysis. We have identified this rare hemoglobinopathy in an Argentinean girl with severe hemolytic anemia, splenomegaly and frequent requirement for red blood cell transfusions.